2014
DOI: 10.2106/jbjs.l.01527
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Changes in Patients with Pseudarthrosis After Posterior Lumbar Interbody Arthrodesis Using Carbon Interbody Cages

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Faster bone fusion occurred with the combined PRP graft, but plain radiographs did not show an overall increase in fusion; however, this may be because it is difficult to evaluate spinal fusion on plain radiographs only. 14 There may also have been bias in the comparison of prospective and historical cohort data, and therefore further investigation of the efficacy of PRP is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faster bone fusion occurred with the combined PRP graft, but plain radiographs did not show an overall increase in fusion; however, this may be because it is difficult to evaluate spinal fusion on plain radiographs only. 14 There may also have been bias in the comparison of prospective and historical cohort data, and therefore further investigation of the efficacy of PRP is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The endpoints for evaluation were the area and mean density of bone fusion after PLF surgery on computed tomography (CT) at 2 weeks and 3, 6, and 12 months after surgery. For definition of successful fusion, we also evaluated the segmental range of motion under 5° on lateral flexion-extension radiographs with no radiolucent zones surrounding the pedicle screws on CT, 14 as well as continuous fusion mass formation between transverse processes on CT. For 10-year follow-up, all patients underwent plain radiography, CT, and magnetic resonance imaging at an outpatient clinic for evaluation of clinical symptoms and adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the CT scans in the pseudarthrosis group were performed after a premature FU of only 9.9 months following the index surgery in comparison to 20.4 months in the cohort of patients without pseudarthrosis. Previous studies have, however, pointed out that significantly longer FU is required for an appropriate fusion assessment, and in these particular cases, the term 'delayed union' may be more appropriate than the term 'pseudarthrosis' [71][72][73].…”
Section: Interbody Fusion Assessmentmentioning
confidence: 99%
“…Based on the results of 5-year follow-up examinations, they reported that a radiolucent zone of more than 1 mm around the interbody cage at the 12-month mark was shown to be an early predictor of permanent pseudarthrosis in their cohort. 35 Similarly, Shah et al 56 reported that bridging trabeculation was appreciated on 95% of CT scans (k = 0.85) versus 4% on plain films (k = 0.74) for patients with lumbar interbody fusion. Based on these findings, the authors also suggest that thin-section CT scans should be the modality of choice for the early detection of pseudarthrosis.…”
mentioning
confidence: 98%
“…7,22 While there are no universally accepted criteria for assessing interbody bone fusion, most studies use all or some of the following features for defining pseudarthrosis: complete absence of continuous bony trabeculation between adjacent vertebrae, peri-implant radiolucency, and/or motion on dynamic films. 35,56,57 Early studies using CT scans have shown 57% to 80% correlation between fusion assessments based on imaging versus intraoperative findings, with 53% to 63% sensitivity and 78% to 86% specificity. 7,42,54 Since then, there have been considerable advancements in CT technology with the introduction of thin-section axial sequencing and 3D imaging (Fig.…”
mentioning
confidence: 99%